2005
DOI: 10.1182/blood-2005-03-0889
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pathologic retinal neovascularization by  -defensins

Abstract: Proliferative retinopathies, such as those complicating prematurity and diabetes, are major causes of blindness. A prominent feature of these retinopathies is excessive neovascularization, which is orchestrated by the hypoxia-induced vascular endothelial growth factor (VEGF) stimulating endothelial cells and the integrin-mediated adhesive interactions of endothelial cells with extracellular matrix components such as fibronectin (FN). Recently, we demonstrated that ␣-defensins interfere with ␣5␤1-FN interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 42 publications
(62 reference statements)
2
78
0
1
Order By: Relevance
“…Moreover, HNP can form a ternary complex with fibronectin and a 5 h 1 integrin and further affect endothelial cell adhesion, migration, and proliferation (10). HNP have also been shown to attenuate endothelial permeability and proliferation stimulated by the vascular endothelial growth factor and fibroblast growth factor in vivo (9). In this study, a lower density of vessels was found in tumor tissues treated with pSec-HNP1 by anti-CD31 staining, which indicates that tumor angiogenesis is effectively inhibited.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Moreover, HNP can form a ternary complex with fibronectin and a 5 h 1 integrin and further affect endothelial cell adhesion, migration, and proliferation (10). HNP have also been shown to attenuate endothelial permeability and proliferation stimulated by the vascular endothelial growth factor and fibroblast growth factor in vivo (9). In this study, a lower density of vessels was found in tumor tissues treated with pSec-HNP1 by anti-CD31 staining, which indicates that tumor angiogenesis is effectively inhibited.…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies have shown that HNP1 has an effect on angiogenesis via affecting endothelial cell in pathologic retinal neovascularization and inflammation (9,10). To investigate its role in tumor angiogenesis, we did immunohistochemical staining with anti-CD31.…”
Section: Inhibition Of Tumor Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of VEGF or its kinase receptors (VEGFRs) can cause normalization of tumor vasculature (20,21). It is reported that HNP1 could impair VEGF-mediated angiogenesis (19,28). In the present study, to avoid the influence of the plasmid vector on angiogenesis, a mature HNP1 peptide was injected intratumorally in the 4T1 tumors and normalized microvessels of orderly formed EC monolayer were observed after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of VEGF or its kinase receptors (VEGFRs) could result in tumor vasculature normalization (20,21). It has been reported that HNP1 impairs VEGF-mediated angiogenesis (19,28). To detect the influence of HNP1 on tumor microvessels, a commercial HNP1 peptide was injected intratumorally, and ultrastructural changes were observed by transmission electron microscopy.…”
Section: Intratumoral Expression Of Hnp1 Promotes Tumor Microvessel Nmentioning
confidence: 99%